"Sistema de control interno de hardware y software para equipos de cómputo de la Universidad Técnica Estatal de Quevedo" - Campuzano Arechua, Guillermo Armando (2014)
The maintenance and updating of computer equipment UTEQ had a number of problems, de not having a proper inventory management and record equipment functionality. So the functionality that had not tasted, upgrades and maintenance that should be perdemed. The following tabla presents a solution to control IT as set swill helps improve the efficiency and optimization of all processes to prevent problems by providing status indemàstion and functionality of the equipment. By perdeming a stock control module, the implementation of a monitoring mechanismo perating update alerts and developing web services that allows obtains the status of equipment functionality. After completion of the implementation and supporting evidence to the staff of the institution, it was shown that using the Control System hardware and software UTEQ allowed having a total surveillance over the IT as sets you have and get the institution status indemàstion of the equipment quickly and reliably meet the needs of the University community